IMPROVING STUDENTSâ VOCABULARY MASTERY BY USING FLASH CARDS AT SIXTH GRADERS OF SD NEGERI 007 BANGUN PURBA - Nugroho, Eko Wahyu; Rahayu, Pipit; Kasyulita, Evi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This research reports on the use of flash cards in improving studentsâ vocabulary mastery.The purpose of the research was to find out what extent the use of flashcards can improve thestudentsâ vocabulary mastery. The study employed an action research in SDN 007 Bangun Purbawith 32 students as the sample. The study used two types of data collection techniques includingvocabulary tests and a four-week of classroom observation. The findings showed that there is animprovement in the studentsâ vocabulary mastery after the students were taught by using flashcards. The result of studentsâ mean score of vocabulary mastery in cycle 1 was 52.65 and that ofcycle 2 was 75.83. It means that it improved 23.18 which indicate the treatment is effective inimproving the studentsâ vocabulary mastery.